Provisions for The Use of Foreign Workers in Indonesia - Flambonita, Suci; Emilda Kuspraningrum; Suartini (Universitas Muhammadiyah Bima, 2023)
The use of foreign workers in Indonesia is intended to transfer knowledge and SKILL. Various requirements must be met as a condition if the entrepreneur/company wishes to bring in foreign workers. The purpose of placing foreign workers in Indonesia; first, is to meet the need for skilled and professional workers in certain fields that cannot be filled by Indonesian Migrant Workers; second, accelerating the process of national development by accelerating the process of technology transfer or knowledge transfer, especially in the industrial sector; third, provide expansion of employment opportunities for Indonesian Migrant Workers; fourth, increase foreign investment as a support for development capital in Indonesia. This type of research uses normative methods by analyzing legal provisions with statutory and case approaches, is descriptive analysis in nature which aims to describe, inventory, and analyze regarding the provisions governing foreign workers in Indonesia through library research. The discussion in this study is an effort to avoid legal problems and the excessive use of foreign workers, the government must carefully determine the policies to be taken in order to maintain a balance between foreign workers and domestic workers. The manpower aspect, especially in terms of the obligation to use Indonesian workers and the necessity to hold industrial training, transfer of knowledge and technology as well as work permits for foreign workers is an absolute requirement in relation to the use of labor.